Islet autoantibodies and residual beta-cell function in children with type 1 diabetes depending on age of manifestation - E. M. Romanenkova; I. M. Zufarova; D. Y. Sorokin; I. A. Eremina; E. A. Sechko; L. V. Nikankina; V. A. Peterkova; O. B. Bezlepkina; D. N. Laptev (Сахарный диабет)
BACKGROUND: Type 1 diabetes mellitus (T1D) is an autoimmune disorder that leads to pancreatic β-cells destruction and progressive decrease of insulin secretion. Specific islet autoantibodies (AAbs) are the main diagnostic marker of T1D. Residual β-cell function, as measured by C-peptide, has repeatedly been demonstrated to be clinically important.AIM: To study the frequency and levels of residual C-peptide secretion and persistence of pancreatic AAbs in children with T1D with different duration and age of manifestation of the disease.MATERIALS AND METHODS: The levels of C-peptide and AAbs to ZnT8 (zinc transporter 8), AAbs to IA-2 (Insulinoma Antigen 2), AAbs to GAD (Glutamate Decarboxylase), IAA (insulin autoantibodies) were measured. Patients were divided into 3 groups depending on the duration of T1D (1st — <1 year, 2nd — from 1 to 5 years, 3rd — >5 years) and age of manifestation (A — prepubertal and B — puberty).RESULTS: The median duration of T1D was 1.8 [0,8;3,9], 76.3% out of 1333 patients were seropositive, 40% had residual levels of C-peptide. With disease duration there were a decrease in AAbs+: 1st group 74%, 2nd group 69%, and 3rd group 48%. In all groups, percentage of patients with positive levels of one or more AAbs was significantly higher in children with T1D manifestation at puberty. GADA and ZnT8A were more common in the first year of the disease. IA-2A were observed with the same frequency in the group of adolescents. IAA were more common in patients at prepubertal age. An undetectable level of C-peptide was observed significantly higher in children with T1D manifestation in prepubertal age (p<0.05): 1А — 13% and 1B — 5%, 2А — 51% and 2B — 14%, 3А — 82% and 3B — 50%, reference range of C-peptide was observed in adolescents (p<0,05): 1А — 6% and 1B — 44%, 2А — 2% and 2b — 25%, 3А — 2% and 3B — 11%.CONCLUSION: AAbs+ is relatively common in children with T1D and about half of them are seropositive in more than 5 years after manifestation. GADA and ZnT8A have high specificity for patients with new-onset T1D. C-peptide secretion depends on the age of the disease manifestation.